2006
DOI: 10.1590/s0102-311x2006001000010
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal infection and adverse pregnancy outcomes: a systematic review of epidemiological studies

Abstract: The objective of this systematic review was to evaluate analytical studies on periodontal disease as a possible risk factor for adverse pregnancy outcomes. A literature search of the MEDLINE, SciELO, and LILACS bibliographic databases and CAPES thesis database was conducted up to December 2005, covering epidemiological studies of periodontal disease and adverse pregnancy outcomes. Of the 964 papers identified, 36 analytical studies met the inclusion criteria. Twenty-six epidemiological studies reported associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0
5

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(55 citation statements)
references
References 39 publications
(108 reference statements)
0
50
0
5
Order By: Relevance
“…A systematic review of epidemiological studies 211 found no sound scientific justification to recommend routine screening for…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…A systematic review of epidemiological studies 211 found no sound scientific justification to recommend routine screening for…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…Les mesures pour évaluer l'atteinte parodontale varient égale-ment d'une étude à l'autre. Certains auteurs utilisent le CPITN qui est considéré comme non adapté pour l'évaluation de la sévérité et de la prévalence de la maladie parodontale dans les études cliniques [45]. Le CPITN donne une évaluation globale alors que la classification des parodontopathies est complexe et précise.…”
Section: Définition Et éValuation De La Maladie Parodontaleunclassified
“…Dans la revue de littérature de Vettore et al, parue en 2006, on constate que peu d'études prennent en compte les facteurs de risque [45]. Dans la méta-analyse réalisée par Vergnes et al [7], les 17 études analysées prennent en compte de 6 à 14 facteurs de risque sur les 43 décrits par Vettore et al [45]. Des auteurs excluent de leur échantillon certaines femmes [20,31,40] (patientes ayant un diabète, une maladie cardiovasculaire, un asthme, etc.)…”
Section: Prise En Compte Des Cofacteursunclassified
See 2 more Smart Citations